O humor no ambiente escolar: A inserção do cartum, da charge e caricatura no processo de ensino das artes visuais - SILVA, Aerlon Charles Araújo e (2023)
This article presents the result of the Humor at School Project, an artistic creation process developed and carried out in the classroom on reading, production and contextualization of cartoons, cartoons and caricatures in visual arts classes with 1st year students of the Institute's Administration course Federal Institute of Science and Technology Education of Piaui, Pedro II campus. We set out to investigate the teaching of art in Brazil and its historical course. We observe how the teaching/learning process took place in the on-site research after the students' artistic productions were carried out with graphic humor drawing. A brief history of the two main humor salons in Brazil was also revisited. The research was applied in a participatory qualitative way, with a methodology based on action research of an artistic/pedagogical nature, identifying the facilities and difficulties encountered in the teaching process in arts and aspects regarding the use of the Triangular Approach. We conclude with the artistic productions of the students resulting from the action of the Humor at School Project workshop.